'I shall show you the right path': Samuil Lur'e and the first Russian film journal, Sine-Fono. (4th May 2018) - Kovalova, Anna
Abstract: This article is dedicated to the first Russian film journal, Sine - Fono, which was published from 1907 to 1918. Sine - Fono was a leading periodical for more than ten years and it played a crucial role in the pre-Revolutionary cinematic process. The journal Sine - Fono is interesting not only as a key fact of the history of early Russian cinema, but also as an extremely important source for its study: since the overwhelming majority of pre-Revolutionary Russian films have not been preserved, historians must judge this period in Russian film history primarily by means of the film press. The article also explores the fate, both before and after the Revolution, of the founder and constant editor of the journal, Samuil Lur'e.